Design of peptide ligands for affinity purification of human growth hormone. Issue 7 (11th May 2019) - Chandra, Divya; Timmick, Steven; Goodwine, Chaz; Vecchiarello, Nicholas; Shastry, Divya G; Mullerpatan, Akshat; Trasatti, John P; Cramer, Steven; Karande, Pankaj
Abstract: Background: In this study, we have demonstrated the design, screening and selection of peptide ligands for the affinity capture of human growth hormone (hGH) from yeast cell cultures. Results: Ligand design was carried out using multiple approaches based on primary sequence and structures of natural binding partners of hGH. Screening of potential affinity peptides was conducted using high throughput microarray platforms followed by assessment of in‐solution binding to hGH using fluorescence polarization. Peptide leads were subsequently immobilized on chromatographic resins and the binding and desorption behavior was examined using batch adsorption studies. A lead candidate was examined in further details in column chromatography studies which indicated that while high purity was attained, further refinement was necessary for improved product recovery. Histidine scanning was employed to successfully improve the recovery of hGH from cell culture fluid while still maintaining high purity. Finally, proof‐of‐concept was demonstrated in the column format using complex feed stock where a product purity of 95% was attained at 80% yield. Conclusion: The approaches presented here can be translated to other biologics of interest for the rapid development of affinity based purification processes. © 2019 Society of Chemical Industry